AI-DRIVEN SAFETY INNOVATIONS IN AUTONOMOUS VEHICLES: A TECHNICAL ANALYSIS - Rajaesh Kamisetty, (INTERNATIONAL JOURNAL OF RESEARCH IN COMPUTER APPLICATIONS AND INFORMATION TECHNOLOGY (IJRCAIT), 2024)
Autonomous vehicle technology stands at the forefront of transportation innovation, with artificial intelligence (AI) serving as the cornerstone of safety enhancements. This technical article examines how AI technologies are revolutionizing self-driving capabilities through advanced perception, decision-making, and control systems. Current data indicates that AI-powered autonomous vehicles achieve a 37% reduction in collision rates compared to human-operated vehicles, primarily through multi-layered perception systems processing 1.5 terabytes of sensor data per hour and decision-making algorithms operating at 320 TOPS. The analysis reveals significant improvements in safety metrics, including a 94% effectiveness in primary collision prevention and 97% pedestrian incident prevention. Integration of sophisticated sensor fusion technologies, including LiDAR systems with 360° coverage and 128 scanning layers, high-resolution cameras operating at 120 fps, and radar arrays detecting objects up to 300m away, enables comprehensive environmental awareness. Deep learning architectures, processing 250,000 different driving scenarios per training iteration, achieve real-time object detection with 98.5% accuracy for vehicles and 96% for pedestrians. The article demonstrates how fail-safe mechanisms and redundant systems achieve 99.9999% reliability, with Mean Time Between Failures (MTBF) of 50,000 hours. The article also explores future developments, including Neural Processing Units projected to reach 1,000 TOPS by 2025 and enhanced V2X communication targeting sub-5ms latency, marking crucial steps toward safer autonomous transportation systems.